Survey for parasites of Sesamia calamistis(Lep.:noctuidae) and Eldana saccharina (Lep.:pyralidae) in southwestern Nigeria - Bosque Pérez, N.A.; Ubeku, J.A.; Polaszek, A. (1995)
Field surveys were conducted during 1990–92 to document the relative abundance of different species of parasites of the lepidopterous stem borers Sesamia calamistis Hampson and Eldana saccharina Walker in maize fields in southwestern Nigeria. Species of parasitoids detected on both stem borers included the larval pupal parasitoids Sturmiopsis parasitica Curran (Diptera: Tachinidae) and Brachymeria feae Masi (Hymenoptera: Chalcididae), and the larval parasitoid Dolichogenidea polaszeki Walker (Hymenoptera: Braconidae). The braconid Cotesia sesamiae (Cameron) was found attacking S. calamistis. The hyper parasitoid Exoristobia dipterae (Risbec) (Hymenoptera: Encyrtidae) was detected on a pupa of S. parasitica. Parasitic nematodes belonging to Mermis sp. and/or Hexamermis sp. were found infesting larvae of both stem borers. Overall, larval/pupal parasitization levels at Ibadan were low and ranged from 4.2 to 22.8% for S. calamistis and 1.2 to 13% forE. saccharina. Of the parasites found,S. parasitica was the most common, followed by nematodes. Four hymenopteran egg parasitoids were found attackingS. calamistis: Telenomus busseolae Gahan,T. isis Polaszek (Scelionidae), Lathromeris ovicida Risbec, and Trichogrammatoidea eldanae Viggiani (Trichogrammatidae). Egg parasitization ranged from 13.4 to 41.5%. The only egg parasitoid detected onE. saccharina was Telenomus applanatus Bin and Johnson, which inflicted only 5% parasitization.